Experimental analysis of a sensitive plate for grain loss monitoring system - Muhammad Isa, Bomoi; Mat Nawi, Nazmi; Abd Aziz, Samsuzana; Mohd Kassim, Muhamad Saufi; Al Riza, Dimas Firmanda (Northeastern University, 2023)
The ability to monitor grain loss from a combine harvester during harvest is an important element in rice production to minimize grain loss. In this study, an experimental modal analysis was performed to evaluate the effect of the dynamic behavior of a stainless-steel plate at four different thicknesses to determine the desirable plate thickness for developing a sensitive plate for a grain-loss monitoring system. The plates were 250 mm long and 180 mm wide, and their respective thicknesses were 1, 1.5, 2, and 2.5 mm with each plate containing 78 measurement points. Modal analysis was performed using an impact hammer, piezoelectric accelerometer sensor, national instrument data acquisition device, and MEscope analysis software. For the experiment, the piezoelectric accelerometer sensor was fixed to the center of the plate as the output device, whereas the impact hammer was set to strike three impacts per measuring point on the plate as the input device. The recorded sensor signals were imported into modal analysis software for the extraction of modal parameters. The findings were further evaluated using a Bode plot to determine the frequency response performance of the plates, and polynomial model fitting analysis to compare the significance of the modal properties of the plates. According to the results of the analysis, a 1.5 mm plate thickness was chosen as the appropriate plate thickness for the grain loss monitoring system.